Study Penempatan Shearwall terhadap Stabilisasi Gedung Walikota Mataram dengan Menggunakan Aplikasi SAP 2000 - Andika Prakoso; Hafiz Hamdani; Ahmad Zarkasi (Universitas Batanghari Jambi, 2026)
The Mataram Mayor's Building, West Nusa Tenggara, consists of 3 floors with a total height of 14.25 m. All floors of the building use reinforced concrete structures, which make them vulnerable to lateral forces, especially those caused by earthquakes. Earthquakes risk causing building damage, therefore a special frame-bearing structure is needed to withstand earthquake forces to prevent structural failure, therefore shear walls are needed to withstand lateral forces. The placement and shape of shear walls affect the building's ability to withstand lateral forces. The problem of researchers in this study is how to compare the effectiveness of the four variations of shear walls when resisting lateral forces. So that researchers get the goal of knowing the value of floor deviations in the x and y directions and knowing the optimal placement location point in resisting lateral forces. In this study, a general type of data collection method is used, namely data collection carried out by collecting working drawings from project service providers. Based on the results of the analysis of the four existing models, it can be concluded that the placement of the shear wall position is more effective if placed at the right corner of the L-shaped building, if viewed from the results of the floor deviation values in the x and y directions. Where the overall floor deviation in the x direction of variation 1 is 1.12 mm, while the deviation in the y direction is 2.80 mm.